Use of Self-Determination theory in explaining antenatal care Booking: A Cross-Sectional study - Maximillian B. Tungaraza; Angelina A. Joho (Elsevier, 2022)
Background: Timely antenatal booking is of utmost importance for early identification, prevention of pregnancy-related complications, proper management, and on-time referrals. Objective: This study aims to assess the use of self-determination theory in explaining timely antenatal care (ANC) booking among postnatal women. Methods: A hospital-based cross-sectional study was conducted in three district hospitals and ten health centers in the Mara region. The study was conducted from April to July 2020 among 384 postnatal women who were randomly selected using a multi-stage sampling technique. We used a self-administered questionnaire to collect the required data. Data were analyzed using SPSS version 20. Chi-square and Fisher's exact tests were used to assess the association between categorical variables. Binary logistic regression analysis was performed to determine the predictors of timely ANC booking. A p-value of <0.05 was considered statistically significant. Results: Of 384 respondents, 77.1% had late ANC service booking and 53.4% were self-determined. High perceived autonomy (AOR = 2.36, 95% CI = 1.33-4.18, p = 0.003), being employed (AOR = 5.64, 95% CI = 1.42-22.35, p = 0.014], self-employment (AOR = 5.97, 95% CI = 1.57-22.66, p = 0.009), and being advised by relatives (AOR = 2.50, 95% CI = 1.25-4.98, p = 0.009) were associated with timely ANC booking. Conclusion: The majority of study participants showed to have late ANC booking. Factors influencing timely ANC booking in this study included high perceived autonomy, employment, and advice for family members. Women should be empowered through the provision of ANC education, and enhancement of community awareness regarding timely booking for ANC services. Also, increasing the number of skilled birth attendants, and using appropriate communication skills among health care providers may help to increase their self-determination among postnatal women towards timely ANC booking.